"An Unhappy Interlude": Trivialisation and Privatisation of Forced Marriage in Asylum-Seeker Women's Cases in the UK. (19th July 2022) - Honkala, Nora
Abstract: This article examines asylum-seeker women's appeals involving forced marriage at the Upper Tribunal (Immigration and Asylum Chamber) in the UK over the past 20 years. Internationally forced marriage has long been understood as a human rights issue. In the UK, the government has introduced a range of policy and legislative measures to tackle forced marriage of its nationals that have been framed within human rights discourse. The aim of this article is to examine the ways in which forced marriage has been framed by the Tribunal in women's asylum claims. Informed by feminist contributions to gender and refugee law, the article reveals two problematic and interrelated trends. First, that gendered harm in the form of forced marriage continues to be contained in the "private" sphere. And secondly, that a noteworthy trend of trivialisation through conflation of forced and arranged marriage, and the use of euphemisms emerges. As a result, these gendered representations evidence a continuing failure of refugee law to take women's rights violations seriously.